Philippine Economic Update : Accelerating Reforms to Meet the Jobs Challenge - World Bank (Washington, DC, 2014)
The Philippine economic update provides an update on key economic and social developments, and policies over the past 6 to 12 months. It also presents findings from recent World Bank studies on the Philippines. The Philippine economy expanded by 6.6 percent in 2012, exceeding most expectations, including the government's own target of 5 to 6 percent. The pace and efficiency of national government spending improved remarkably in 2012. Higher government spending was matched by a significant increase in revenue collection, with a strong contribution from improved tax administration. Total tax revenues grew by 13.2 percent and tax effort increased from 12.3 to 12.9 percent of Gross Domestic Product (GDP)-the highest increase in decades attributable to improved tax administration. The medium-term growth prospects for the Philippines are good. GDP growth is projected at 6.2 percent in 2013, driven by domestic demand. There is no silver bullet for creating more and better jobs, as it is linked to resolving deep-seated, structural issues in the economy. Only a comprehensive reform agenda implemented across sectors can foster a business environment conducive to private sector job creation by firms of all sizes. A unique window of opportunity exists today to accelerate reforms that will help create more and better jobs.